Identifikasi Cacing Polychaeta, Nereis sp. sebagai Vektor White Spot Syndrome Virus (WSSV) di Alam dan Kajian Uji Tantangnya di Laboratorium - Bambang W. Prastowo; Kade Ariawan; Evy M. Nur; Rahayu Rahardianti; Yuni Setyowati (Universitas Gadjah Mada, 2009)
Polychaete worm is an important zoobenthos at shrimp culture system, however since there is no any culture of these worm in Indonesia, then all the worm biomass collected from their natural habitat. It raised some concern about their safety because polychaete worm might be get infected and will realistic as a pathway for virus to attack shrimp broodstock in the hatchery. Fresh polychaete worms (1 g wet) used as a test organisms were caught from pond area in Semat region, Jepara. The step of these experiment are identification of WSSV infection at polychaete worms in wild with PCR analysis, visual, microscope and histology observation. Followed by challenge test of polychaete worm with WSSV, and WSSV infectivity study at black tiger shrimp broodstock. It seen, from the experiment, that using two different PCR methods, OIE (2006) and Nugen kit, and also histology analysis showing no WSSV infection in polychaete worms. However, from further experiment showing that polychaete worm challenge by WSSV have already got severely stress due to WSSV inocculum treatment, but the level of infection is still very low so that can not detect by PCR. Shrimp broodstock that have already fed with WSSV-contaminated polychaete worms for 1 week, based on clinical signs seems to get infected by WSSV, even the infectivity level is still very low. It concluded that polychaete worm can be a vector for WSSV in pond.